(untitled) (Journal of Foreign Language Studies, 2021)
Currently there is a strong need for English language learning in general and mobile English language learning in particular among Vietnamese teenagers. Nonetheless, there are few studies about the effectiveness of using mobile devices (MD) for learning, including English language learning by this target group of learners. This paper presents the results of a study on purposes of using MD and the differences between school and university students in their mobile English language learning. The study utilized mix-methods approach, descriptive and inferential techniques to analyse data collected from 655 surveys and 23 interviews with students in three regions: northern, central and southern Vietnam. The study findings revealed that teenagers used MD for entertainment, information searching the most and online learning the least. There are differences between rural and urban, school and university as well as between English and non-English majored students in their prior experience with online English language learning and current usage of MD for online learning. Both school and university students perceived that MD could be effectively used to enhance listening, reading and speaking skills, but the device was not as useful for writing skills. The study suggests that it is necessary to develop software and applications with suitable content for this target group of learners in order to further enhance the quality of mobile English language learning in Vietnam.